Measure’s of the Indian Government in Combating Illegal Wildlife Trafficking: A Green Theory Approach from a Post-Positivist Perspective in International Relations Departments - Nada AQILA; Abdul Khakim Mahfud ZUBAIDI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This analysis aims to provide both academic and practical benefits by offering a comprehensive evaluation of India’s policies on combating illegal wildlife trafficking. By integrating sustainability principles and addressing the challenges faced in enforcement and economic growth, the study contributes valuable insights into how the country can enhance its efforts in wildlife conservation. The findings also offer broader implications for strengthening international collaborations, improving law enforcement mechanisms, and reinforcing the role of global environmental norms in shaping national policies. Ultimately, this research seeks to advance both theoretical understanding and practical applications in the field of environmental diplomacy and wildlife protection.Methodology:This research employs a qualitative descriptive approach and a case study method to examine India’s legal framework in combating illegal wildlife trafficking.Findings:India has adopted a norms-based approach and international cooperation in combating illegal wildlife trade but still faces challenges in implementation due to tensions between economic development and environmental sustainability, weak law enforcement, and the need for greater community involvement in conservation.Implication:The implications of these findings indicate that the success of India's policies in combating illegal wildlife trade hinges on balancing economic interests with a firm commitment to environmental sustainability. Moreover, strengthening law enforcement capacity and enhancing public participation is essential to ensuring that the formulated policies can be effectively implemented at both domestic and international levels. For other nations, India's approach can serve as a model for integrating environmental policies into foreign policy, particularly through international cooperation and institutional reinforcement.